Control Engineering: MATLAB Exercises - Keviczky, László; Bars, Ruth.; Hetthéssy, Jenő.; Bányász, Csilla; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
This MATLAB exercise book accompanies the textbook Control Engineering, providing a platform for students to practice problem solving in the analysis and design of continuous and discrete control problems reflected in the main textbook. The book starts off with a brief introduction to MATLAB, control toolbox and Simulink. Subsequent chapters include a short theoretical summary of the topic followed by exercises on solving complex problems using MATLAB commands. These exercises are ideal for students in computer laboratory classes.
Introduction to MATLAB -- Introduction to MATLAB Control System Toolbox and Simulink -- Analysis of systems in the time-, operator- and frequency domain -- Typical elements of a linear system -- State space description of linear systems -- Feedback and closed loop control structures -- Stability -- Controller design considerations in the time and in the frequency domain -- Control of stable processes -- Series PID Compensation -- State feedback control -- Controlling unstable processes -- Discrete-time systems -- Control of stable discrete -time (sampled data) systems -- Discrete PID control -- State space representation of discrete systems -- State feedback control of discrete systems -- Case study.
Keywords: Control engineering; System theory; Control theory; Application software; Control and Systems Theory; Systems Theory, Control; Computer and Information Systems Applications